NMG expands NA distribution (Reinforced Plastics, 2016)
Abstract Nurses have up to four times more patient contact than physicians, positioning them as central drivers of communication in health care. Effective communication directly influences patient outcomes, teamwork, staff engagement, and the overall care experience. Today's nurses operate within a highly diverse environment that includes four generations in the workforce and up to eight generations of patients, each with distinct values, expectations, and communication preferences. This article examines how generational differences shape communication across three key relational domains: peer-to-peer, nurse-to-patient, and nurse-to-leader interactions, and offers insights to strengthen collaboration, engagement, and quality of care.